2022
DOI: 10.1016/j.jnma.2021.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and outcomes of monoclonal antibody infusion for COVID-19 in an inner-city safety net hospital: A South-Bronx experience

Abstract: Background Monoclonal antibody therapy (MAT) is recommended in mild to moderate Coronavirus disease 2019 (COVID-19) patients who are at risk of progressing to severe disease. Due to limited data on its outcomes and the logistic challenges in administering the drug, MAT has not been widely used in the United States (US) despite of emergency use authorization (EUA) approval by the Food and Drug Administration (FDA). Aim We aim to study the outcomes of MAT in patients pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Sotrovimab, as with other monoclonal antibody therapies authorized for use in patients with COVID‐19, requires intravenous administration, and thus coordinating timely care can be difficult, particularly in areas with limited resources and drug supply. 16 NR use in SOTR poses the specific challenge of managing drug–drug interactions with commonly used immunosuppressive medications. 9 Although the previously published NYPH protocol can effectively help manage the ritonavir‐related drug interactions, this protocol requires intensive therapeutic drug monitoring and should not be followed if drug levels cannot be adequately measured over time.…”
Section: Discussionmentioning
confidence: 99%
“…Sotrovimab, as with other monoclonal antibody therapies authorized for use in patients with COVID‐19, requires intravenous administration, and thus coordinating timely care can be difficult, particularly in areas with limited resources and drug supply. 16 NR use in SOTR poses the specific challenge of managing drug–drug interactions with commonly used immunosuppressive medications. 9 Although the previously published NYPH protocol can effectively help manage the ritonavir‐related drug interactions, this protocol requires intensive therapeutic drug monitoring and should not be followed if drug levels cannot be adequately measured over time.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple studies have reported on the real-world effectiveness of CAS+IMD [4][5][6][7][8][9][10][11][12][13][14][15][16], most only included a small number of CAS+IMD-treated patients, generally evaluating the early experience with monoclonal antibodies (mAbs), were single-center, and did not have sufficient sample size to assess effectiveness of CAS+IMD across various patient subgroups. Studies leveraging large databases with sufficient counts to assess the effectiveness of CAS+IMD in subgroups of patients at higher risk of poor outcomes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In vitro studies suggested that CAS+IMD retains neutralization activity against most VOC including Delta but with the exception of Omicron (B.1.1.529). 5,[13][14][15][16][17] Most real-world studies assessing the effectiveness of CAS+IMD for treating COVID-19 [18][19][20][21][22][23][24][25][26][27][28][29][30] were conducted prior to Delta, and those that did overlap with the emergence of the Delta variant were single-center and of small sample size. 19,30,31 Furthermore, with the introduction of COVID-19 vaccines, an improved understanding of vulnerable groups, and the emergence of the Delta variant, it became important to evaluate the effectiveness of CAS+IMD across these patient subgroups.…”
Section: Introductionmentioning
confidence: 99%